Summer 2009 wildfires in Portugal: Emission of trace gases and aerosol composition - Alves, Célia (2011)
In summer 2009, emissions of trace gases and aerosols from several wildfires occurring in Portugal were sampled. A portable high-volume sampler was used to collect sequentially, on quartz fibre filters, coarse (PM2.5–10) and fine (PM2.5) smoke particles. Tedlar air sampling bags have been used for complementary chemical characterisation of the gaseous phase. The carbonaceous content (elemental and organic carbon, EC/OC) of particulate matter was analysed by a thermal-optical transmission technique. The levels of almost 50 elements were quantified by inductively coupled plasma-mass spectrometry. The water-soluble ions were obtained by ion chromatography. Emission factors of species that are favoured by the smouldering phase (e.g. CO) were above the values reported in the literature for biomass burning in other ecosystems. The CO emission factors were 231 ± 117 g kg−1 biomass (dry basis) burned. Emissions of compounds that are promoted in fresh plumes and during the flaming phase, such as CO2, were generally lower than those proposed for savannah and tropical forest fires. The CO2 emission factors ranged from about 1000 to 1700 g kg−1. Total hydrocarbons, PM2.5, PM10 and OC presented variable emissions, but in general substantially higher than values reported for wildfires in African and Amazonian biomes. The emission factors obtained in Portugal were as follows (in g kg−1 biomass, dry basis): 6–350 for total hydrocarbons, 0.5–42 for PM2.5, 1–60 for PM10, and 0.2–42 for OC (in PM10). The organic carbon-to-elemental carbon ratios measured in the present study largely exceeded those obtained by other researchers. The aerosol mass was dominated by organic matter (OC/PM2.5 = 50 ± 18%, OC/PM2.5–10 = 36 ± 18%). The metal elements represented, on average, 1.23 and 0.91%, while the measured water-soluble ions accounted for 2.6 and 2.1% of the PM2.5 and PM2.5–10 mass, respectively. Carbonates accounted for 0.15–3.1% (average = 0.83%) of PM2.5–10. The dominant elements were B, Ti, Mn, Cu, Zn, Zr and Ba.